Narrative coherence and relational agency: unraveling transitions into and out of Alberta correctional facilities for people living with HIV - Wadams, Morgan; Grekul, Jana; Lessard, Sean; de Padua, Anthony; Caine, Vera (My University, 2024)
Incarcerated populations in Canada face significant health and social challenges during transitions into and out of correctional facilities. These transitions around facilities pose disproportionate barriers to care for people living with HIV. Further research is crucial to comprehend these challenges and reimagine care concepts for people who experience structural marginalization. In this article, experiences of transitions into and out of Alberta correctional facilities for people living with HIV are explored using narrative inquiry. Conducted in a Western Canadian city from 2021 to 2022, the inquiry revolved around two men living with HIV and a history of incarceration. Through co-creating field texts and narrative accounts, their unique experiences of transitions were explored through a collaborative process of analysis. Narrative threads from Bruce and Kyle showcased a lack of narrative coherence and the presence of tensions in their lives, while also emphasizing relational agency. The findings provide avenues for health, social, and justice practitioners who support and care for individuals living with HIV and a history of incarceration to think differently about transitions. By highlighting the importance of attending to the unique identities of individuals and relationships from a position of relational agency, the study advances our understanding of transitions. Recommendations for practice and policy include (a) fostering relational agency among practitioners; (b) challenging conventional views of transitions around correctional settings; (c) incorporating peer-based programming into support services; and (d) reconsidering health, justice, and social systems to better support communities disproportionately affected by high rates of incarceration and HIV.
Keywords: correctional facilities; HIV; narrative inquiry; relational agency; transitions; nursing